Taxonomic revision of the garrulus species group in the bee genus Hylaeus Fabricius, 1793 (Hymenoptera: Apoidea, Colletidae) - Divelec, Romain Le; Michez, Denis (Zootaxa, 2025)
The species group of Hylaeus garrulus (Warncke, 1981) encompasses three rare Iberian endemics. Because of the dubious association of sexes and species concepts, their consistent identification have remained difficult. By the mean of barcoding and morphology, we aim to accurately associate males and females of the group. As a result, H. convergens Dathe 2000 is found to be a junior synonym of H. teruelus (Warncke, 1981) syn. nov., and the female previously assigned to H. teruelus belongs to a new species, H. woodi Le Divelec, sp. nov. This study also revealed that the previous lack of a clear diagnosis for the garrulus group resulted in the erroneous report of H. gazagnairei (Vachal, 1891) in Europe; this species is actually absent from this region. A comparative diagnosis of the garrulus group is therefore provided to facilitate the identification of its members.